Calculating AGC and C/N0 thresholds of mobile for jamming detection - Sakorn, Chotipong; Supnithi, Pornchai (My University, 2021)
GNSS jamming poses a serious threat to GNSS users by interrupting the signal reception and may cause outages. Alleviation and detection of jamming are therefore important issues for real-world users. In this work, we propose the entropy-based detector for mobile phones to detect the jamming occurrence in GPS, Galileo, and Beidou systems. The computed entropy values of the carrier to noise (C/N0) and auto gain control (AGC) are considered as the thresholds. We found that the false alarm of the entropy-based detector is lower than the likelihood ratio test (LRT) by about 4% to 9%.
Keywords: Entropy; GNSS; Jamming detection